2018
DOI: 10.31661/gmj.v7i0.1401
|View full text |Cite
|
Sign up to set email alerts
|

Exercise and Atrial Fibrillation: Some Good News and Some Bad News

Abstract: Atrial fibrillation (AF) is considered as the most common sustained arrhythmia in adults, whose incidence rate is on the rise due to the increase in the mean age of the global population. In recent years, many efforts have been made to identify effective factors in the incidence of AF to prevent them and thereby reduce the consequences of AF. Physical activity is one of the topics that attracted much attention in the last two decades. According to some findings, extreme and prolonged exercise itself can be con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 43 publications
(71 reference statements)
0
2
0
Order By: Relevance
“…Additionally, it may be advantageous for controlling blood sugar, arterial stiffness, sympathetic drive, and the structure of the heart-particularly the left atrium, which is prone to atrophy. Research has indicated that regular engagement in physical activity can lower the frequency of atrial fibrillation (AF) episodes [56]. Itʹs crucial to remember, though, that research points to a possible increased risk of AF in relation to vigorous physical exercise.…”
Section: Physical Activity and Afmentioning
confidence: 99%
“…Additionally, it may be advantageous for controlling blood sugar, arterial stiffness, sympathetic drive, and the structure of the heart-particularly the left atrium, which is prone to atrophy. Research has indicated that regular engagement in physical activity can lower the frequency of atrial fibrillation (AF) episodes [56]. Itʹs crucial to remember, though, that research points to a possible increased risk of AF in relation to vigorous physical exercise.…”
Section: Physical Activity and Afmentioning
confidence: 99%
“…As the incidence rates of AF continues to rise, it is necessary to identify and treat the relevant potentially modifiable risk factors [6]. Hypertension, obesity, smoking, and alcohol consumption have been already approved as possible modifiable risk factors; however, attempts for finding new ones are continuing [7][8][9]. Re-GMJ.2018;7:e1416 www.gmj.ir [14,15].…”
Section: Introductionmentioning
confidence: 99%